Rechat: ferramenta para estudo do comportamento de usuários em sistemas de comunicação do estilo Whatsapp - Ribas, Lucian Rossoni (2021)
The spread of misinformation and hate or sexist speech is becoming a signifcant problem, especially on chat apps. Therefore, it is important to study the profles of the users who disseminate this type of information and the possibilities for analysis of these dissemination mechanisms. This paper describes the development of a data collection and processing tool for researchers interested in studying the behavior of users exposed to these contents. This tool provides a web survey panel and a mobile application for collection. Using a chatbot engine, the dashboard enables researchers to confgure the collection to analyze specifc questions. The app maps the basic profle of the participants, allows interaction with the chatbots sent by the researcher and runs on the volunteers’ devices, similar to a real messaging app, like WhatsApp or Telegram. The data is generated when users interact with the application and can be viewed or exported for analysis through the dashboard. Finally, the application of the tool is described through a use case designed as research in a real scenario. Believed that the proposed tool will help scholars from different areas, even without programming knowledge, to understand the mechanisms of fundamental issues in the behavior of users in chat systems for mobile devices.